Simultaneous Quantification of Aflatoxin B1, T-2 Toxin, Ochratoxin A and Deoxynivalenol in Dried Seafood Products by LC-MS/MS - Yijia Deng (Toxins, 2020)
Mycotoxins are secondary metabolites produced by fungi. These contaminate dried seafoods during processing and storage and represent a potential health hazard for consumers. A sensitive, selective and accurate liquid chromatography/tandem mass spectrometry (LC-MS/MS) method was established for simultaneous quantification of four common mycotoxins (aflatoxin B1 (AFB1), T-2 toxin (T-2), ochratoxin A (OTA) and deoxynivalenol (DON)) in dried shrimp, dried fish and dried mussel products. Mycotoxins were extracted from dried seafood samples by acetonitrile/water (85/15, v/v), subjected to ultrasound for 60 min at 20 °C and cleaned up by defatting with n-hexane. The sample matrix affected the linearity of detection (R2 ≥ 0.9974). The limit of detection (LOD) and limit of quantification (LOQ) in dried seafood products varied from 0.1 to 2.0 µg·kg−1 and 0.3 to 5.0 µg·kg−1, respectively. The method was validated by spiking samples with specific mycotoxin levels, and the recoveries, intra-relative standard deviation (RSDs) and inter-RSDs ranged between 72.2–98.4%, 2.8–10.6%, and 5.5–15.4%, respectively. This method was used to analyze 40 dried seafood products purchased from the Zhanjiang seafood market. Results of this product sampling showed that while no DON was detected, AFB1, T-2 and OTA were detected in 30.8%, 17.5% and 33.3% of the samples, respectively. AFB1, T-2 and OTA concentrations varied at 0.58–0.89, 0.55–1.34 and 0.36–1.51 µg·kg−1, respectively. Relatively high frequency of contamination and the presence of AFB1, OTA and T-2 residues indicate the need to monitor mycotoxins in dried seafood products.